Pengaruh Upah, Keselamatan dan Lingkungan Kerja Terhadap Kinerja Karyawan PT Amanah Enam Berlian Di Bengkulu - Uly, Nata Satria; Ferdiansyah, Dimas; Saelendra, Daffa; Savella, Frans; Simanjuntak, Alibasyah Rawi (Badan Penerbitan Fakultas Pertanian Universitas Ratu Samban, 2022)
The purpose of this research is to find out how much influence Wages have. Safety and Work Environment on Employee Performance of PT Amanah Enam Berlian in Bengkulu. The variables of this research are Wages, Work Safety and Work Environment. The method used in this research is the distribution of questionnaires, observations, literature studies, and documentary studies. This research is a research with a quantitative approach. The population of this study were all 40 employees at PT. Amanah Six Berlian in Bengkulu with saturated sample technique. The analytical tool used in this research is SPSS. The data analysis method used is multiple linear regression, multiple correlation, coefficient of determination, t test and f test. The results showed that (1) Wages had a significant effect on the performance of PT Amanah Enam Berlian employees in Bengkulu, (2) Work safety had a significant effect on the performance of PT Amanah Enam Berlian employees in Bengkulu (3) The work environment had a significant effect on the performance of PT Amanah Enam Berlian employees. in Bengkulu, (4) Wages, safety and work environment simultaneously affect the performance of employees of PT Amanah Enam Berlian in Bengkulu.